In Memory of Mary Ellen Avery - John Steven Torday (Frontiers Research Topics, 2014)
Mary Ellen Avery was the driving force behind the discipline of Neonatology. She fought against convention when she published her ground-breaking paper in 1959 showing that Hyaline Membrane Disease was caused by lung surfactant deficiency. Up until then it was thought to be an due to amniotic fluid aspiration, as suggested by Hoccheim in 1903. She encouraged her students to think out of the box, as long as we were studying 'something that you couldn't live without'. In addition to being a great clinician-researcher she was a mentor. The article is by her former students writing about their personal experiences under the tutelage of Mel Avery.